2013
DOI: 10.1021/jp310621p
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Studies on Vibrational Energy Relaxation of the CO Stretching Mode of Acetone in Alcohol Solutions

Abstract: The vibrational energy relaxations (VERs) of the CO stretching mode of acetone and its complexes with alcohols are investigated by sub-picosecond pump-probe spectroscopy and molecular dynamics simulation. The time constants of the vibrational energy relaxation of the free acetone and that of the 1:1 complex are 4.4 and 2.3 ps for methanol solvent and 5.2 and 1.8 ps for 1-proponal solvent, respectively. The VER rate is accelerated a few times by formation of the hydrogen bond. This acceleration of the vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The shoulder GSB/SE experiences a much faster monoexponential decay which we attribute to faster vibrational relaxation facilitated by hydrogen bonding to the carbonyl group. The faster decay of the hydrogen bonded carbonyl is consistent with previous ultrafast mid-IR studies, which demonstrated that the vibrational lifetimes of carbonyl groups are sensitive to hydrogen bonding. Specifically, hydrogen bonding to alcohol based donors accelerates vibrational energy relaxation of carbonyl groups. Considering the population decays in the context of previous experiments provides additional support for the assignment of the shoulder peak to the PhQ:1HB species.…”
Section: Resultssupporting
confidence: 87%
“…The shoulder GSB/SE experiences a much faster monoexponential decay which we attribute to faster vibrational relaxation facilitated by hydrogen bonding to the carbonyl group. The faster decay of the hydrogen bonded carbonyl is consistent with previous ultrafast mid-IR studies, which demonstrated that the vibrational lifetimes of carbonyl groups are sensitive to hydrogen bonding. Specifically, hydrogen bonding to alcohol based donors accelerates vibrational energy relaxation of carbonyl groups. Considering the population decays in the context of previous experiments provides additional support for the assignment of the shoulder peak to the PhQ:1HB species.…”
Section: Resultssupporting
confidence: 87%
“…A trajectory for 6 ns was carried out at each iteration step of the sequential sampling for the triethylamine and methanol solution systems. A longer trajectory with 12 ns was performed in each interaction step for 1-propanol solution because the hydrogen bond dynamics is slow . From these trajectories, 30,000 configurations were taken as the MM ensemble; i.e., the MM conformational samples were taken at every 300 fs for triethylamine and methanol and 600 fs for 1-propanol, respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
“…A longer trajectory with 12 ns was performed in each interaction step for 1-propanol solution because the hydrogen bond dynamics is slow. 112 From these trajectories, 30,000 configurations were taken as the MM ensemble; i.e., the MM conformational samples were taken at every 300 fs for triethylamine and methanol and 600 fs for 1-propanol, respectively. The convergence criterion of the QM geometry optimization at each step of the sequential sampling was set to be 5.0 × 10 −4 hartrees/bohr for the largest component of the QM gradient.…”
Section: Computational Detailsmentioning
confidence: 99%